Design and analysis of MIMO antenna for IOT applications. (6th June 2022) - Nagendra, R.; Swarnalatha, S.
In this paper, a novel MIMO antenna of compact split ring resonator (SRR) type with high degree of isolation among four ports on the antenna has been proposed for MIMO multiband applications. It is a triband which operate at frequencies 1.44 GHz (-11 dB), 2.3 GHz (-10 dB) and 4.2 GHz (-245 dB), respectively. This proposed MIMO antenna is designed with meander line for better gain and split ring resonator (SRR) in the form of ring for high isolation between the antenna elements. A loaded stub is used to achieve the resonant frequency. The proposed MIMO antenna was simulated with IE3D EM software by mentor graphics and the features such as impedance view, lower return loss, gain, radiation pattern, VSWR, etc. are measured. The proposed antenna has better gain and provides higher isolation between multiple antenna elements.